The Development Of Flash Card Learning Media in Increasing Students' Learning Motivation in Indonesian Language Learning in Grade 1 SDN 15 Koto Baru - Muhammad Subhan; Dodi Widia Nanda; Fenti Alysa (The Future of Education Journal, 2024)
Based on the author's observations at SDN 15 Koto Baru, especially in class 1, the author found several factors causing students' lack of focus in learning, assumed by several factors in learning, less varied learning media, lack of interest, so that students' learning motivation to participate in the learning process is still low. and paying less attention to the material being conveyed so that students do not really understand what is being conveyed so that students do not really understand what is being conveyed by the teacher. This happens because the learning tools and media used are less attractive, only using media such as blackboards and textbooks. The aim of researchers developing flash card media is to create a learning tool that can increase student motivation through the use of visuals and interactives, facilitate understanding of complex concepts in a way that is easy to understand, and stimulate student interest and motivation in studying subject matter through a fun and interesting learning experience. It can be seen that the students' learning outcomes have reached KKM 70, namely, students' learning outcomes with an average of 80% are categorized as very effective. Meanwhile, students' incomplete learning outcomes with an average of 20% are categorized as ineffective. So that flash card learning media can be applied in the learning process. The results of the analysis included 8 students who completed and 2 who did not complete, with a total of 10 students, the number of students who completed was 8 divided by the number of 2 students multiplied by 100, the result is 80%. In the KBBI, effectiveness is defined as usability, activeness, as well as suitability and the goals to be achieved. Based on the analysis above, it can be concluded that flash card learning media is effective, meaning it can help students improve learning outcomes